Implementation of Load Balancing Per Connection Classifier on Mikrotik for Internet Services at Private Vocational Schools - Dinar Mustofa; Anggit Wirasto; Arif Muttakin; Deuis Nur Astrida; Dhanar Intan Surya Saputra (CV. Media Digital Publikasi Indonesia, 2023)
The Internet network is important because now it has entered the 4.0 era, where all community activities are primarily carried out with the help of the Internet. Therefore, the internet network can also connect. One example of using the Internet is currently needed in the school environment. Teachers and students must carry out learning transformations that are usually paper-based and are presently changing through the Internet. As is the case with all teachers and students in private vocational schools. From the results of observations that have been made, not all teachers and students get good internet service. Then, when checking on the server side, it turned out that the internet network management was not following the standards in the field, so the three ISPs (internet service providers) were not being utilized optimally. One solution emerges from presenting these problems: combining and dividing the burden evenly among the three ISPs. The process of distributing the ISP load evenly is called load balancing. In this study, the load balancing method used is the Per Connection Classifier (PCC) method, which can work optimally. This study's findings indicate that the inefficiencies in internet service provision within private vocational schools are due to suboptimal internet network management practices, leading to the need for more utilization of the available internet service providers (ISPs), and proposes the implementation of load balancing as a solution